Admissibility in Federal Court of Evidence Illegally Seized by State Officers - Alan C. Kohn (Washington University Law Quarterly, 1959)
The purpose of this Article is to examine the problem of use in federal court of evidence illegally seized by state officers, first, by considering the historic basis and past judicial treatment of the problem, and, second, by considering how this "open question" should ultimately be decided by the Supreme Court.
Keywords: Search and seizure